Neutrophils mediate Salmonella Typhimurium clearance through the GBP4 inflammasome-dependent production of prostaglandins - Sylwia D. Tyrkalska (Nature Portfolio, 2016)
The role of guanylate-binding proteins (GBPs) in innate immunity is increasingly recognized. Here the authors show that GBP4 activates inflammasome in zebrafish neutrophils, and that this process is critical for the clearance of Salmonellainfection via prostaglandin D2.